Ct Diagnosis of Fahr's Disease, A Case Report - Antonio Gligorievski (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2018)
Fahr's disease is a rare inherited or sporadic neurological disorder with a prevalence of <1/1,000,000, with a higher incidence reported among males and a typical age of onset in the 4th-6th 3rd-5th decade of life. Fahr's disease, or idiopathic striopallidodentate calcinosis, or idiopathic basal ganglia calcification is a rare clinical entity characterized by bilateral and symmetrical intracerebral calcifications of the basal ganglia, thalamus, dentate nucleus and centrum semiovale in the absence of any metabolic abnormality including hypoparathyroidism.